(untitled) (Research, Society and Development, 2022)
This article presents an analysis of the mapping of academic, theoretical-methodological and thematic interlocutions of groups that research on Youth and Adult Education and Teacher Training of Natural Sciences and Mathematics. The mapping was carried out from the productions presented at the National Meeting of Research in Science Education, using the time space from 2011 to 2021, characterized as a research of "state of the art" methodology. As a result, we had few works involving the themes under study, leaving the certainty of the need to expand the spaces for training teachers of Youth and Adult Education, specifically by areas of knowledge. We observed a growth in studies aimed at teacher training in general, but there is an urgent need to discuss the specificities, both of the EJA, as well as of the areas and their curricular components.